3
$\begingroup$

Consider $$ \sin x -\sqrt 3 \cos x=1 $$ for $0\leq x \leq 2\pi$.

I solved it by converting $\sin x -\sqrt 3 \cos x$ to $2\sin(x-\pi/3)$ as follows

\begin{align*} \sin x -\sqrt 3 \cos x &= r\sin(x-\theta)\\ &= r\sin x\cos\theta -r \cos x\sin\theta\\ \end{align*}

we have \begin{align*} r\cos \theta &= 1\\ r\sin \theta &=\sqrt 3 \end{align*} where $r=2$ and $\theta=\frac{\pi}{3}$ are the solution.

So the equation becomes $$ 2\sin (x-\pi/3) =1 $$ and the solution are $x=\pi/2$ and $x=7\pi/6$.

Is there any other method to solve it?

$\endgroup$
  • 3
    $\begingroup$ You can use the relation $\sin^2(x)+\cos^2 x=1$ to find a quadratic equation in $\sin x$ or $\cos x$. $\endgroup$ – Mhenni Benghorbal Mar 26 '14 at 15:41
5
$\begingroup$

Let me introduce the one and the only, the grandest substitution :

$t=\tan(\frac x 2)$

Now, $\sin(x)=\frac{2t}{1+t^2}$ and $\cos(x)=\frac{1-t^2}{1+t^2}$

Now put them back and solve the quadratic. Find value of $t$. Can you now find x?

Another method : Type the equation here

$\endgroup$
3
$\begingroup$

Squaring you have:

$$\sin^2 x + 3\cos^2x - 2\sqrt{3}\sin x\cos x = 1$$

So, $\cos^2 x = \sqrt{3}\sin x\cos x$

i.e., either $\cos x = 0$, in which case $x = \pi/2$ (since $3\pi/2$ is not a solution) or $\tan x= 1/\sqrt{3}$, in which case $x = 7\pi/6$

$\endgroup$
2
$\begingroup$

You can convert it directly:

$$\sin x -\sqrt 3 \cos x=\sin x -\tan(\frac{\pi}{3}) \cos x=\sin x -\frac{\sin(\frac{\pi}{3})}{\cos(\frac{\pi}{3})} \cos x\\ =\frac{\sin x\cos(\frac{\pi}{3}) -\sin(\frac{\pi}{3})\cos x}{\cos(\frac{\pi}{3})} =\frac{\sin (x-\frac{\pi}{3})}{\cos(\frac{\pi}{3})} $$

In general, when dealing with $\sin(x)\pm A \cos(x)$, to convert it just write $A=\tan(\theta)$.

$\endgroup$
2
$\begingroup$

We know that $\cos{\pi\over3}={1\over2}$ and $\sin{\pi\over3}={\sqrt3\over2}$, so

$$\begin{align} \sin x-\sqrt3\cos x=1&\implies{1\over2}\sin x-{\sqrt3\over2}\cos x={1\over2}\\ &\implies\sin x\cos{\pi\over3}-\cos x\sin{\pi\over3}={1\over2}\\ &\implies\sin(x-{\pi\over3})={1\over2}\\ &\implies x-{\pi\over3}={\pi\over6}\quad\text{or}\quad x-{\pi\over3}=\pi-{\pi\over6}\\ &\implies x={\pi\over2}\quad\text{or}\quad x={7\pi\over6} \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.